The Effect Of Different Altitudes On The Quality Of Mangga (Mangifera indica L.) Variety Gedong Gincu - Apriani, Chairunnisa; Gunawan, Ayu Sabrina; Wahyuni, Siti (Jurnal Agrosci, 2025)
This study aims to determine the effect of different altitudes on the quality of Gedong Gincu mango fruit, and to determine which altitude has better quality of Gedong Gincu mango fruit. The research was conducted at the Laboratory of the Faculty of Agriculture, Universitas Swadaya Gunung Jati Cirebon, West Java. The research was conducted from July to August 2024. The research method used was the survey method, covering Jatibarang District (Krasak Village, Pawidean, and Jati Sawit) as a lowland, and Greged District (Gemulung Tonggoh Village, Jati Pancur, and Lebak Mekar) as a highland. From each altitude, 30 Gedong Gincu mangoes were taken. Variables measured included weight loss, fruit hardness, fruit diameter, total soluble solids, vitamin C content, and organoleptic test. Data were analyzed using two independent samples t-test, and Wilcoxon test for organoleptic. The results showed that differences in altitude made a difference to the 4th day weight loss, total soluble solids content, 4th day vitamin C content, 1st and 4th day hardness, as well as on taste, aroma and consumer preference. Gedong Gincu mango fruit from the lowlands had higher weight loss and total soluble solids than those from the highlands, while vitamin C content and hardness of Gedong Gincu mango fruit from the lowlands were lower than those from the highlands. The flavor and aroma parameters of highland Gedong Gincu mango fruit were preferred over Gedong Gincu mango fruit from the lowlands.